FOREIGN LANGUAGE MOTIVATION OF STUDENTS - Pukevičiūtė, Virginija Jūratė (Acta Paedagogica Vilnensia, 2008)
The article presents the learning to learn concept and gives an overview of the most relevant foreign language motivation theories.The research revealed that the motives having an impact on external foreign language motivation are the domineering ones. It is obvious that students’ instrumental orientation is more significant, foreign language learning being more frequently associated with future prospects, whereas the obligation to receive a credit or to pass an exam are not considered to be of great importance.The research analysis showed correlation between students’ affective level of learning a foreign language and the motives stimulating their external and internal learning motivation. It has become obvious that the desire to visit a foreign country, the lang-uage of which is being studied, as well as the aim to communicate in that language encourage students to get interested in it and help them avoid anxiety during language classes. Besides, the satisfying feeling emerging in the foreign language learning process adds to one’s fulfilling experience and this in its own turn prevents indifference. It is evident that foreign language learning inspires more positive emotions to the respondents while the negative ones are more likely to be caused by the fear of speaking a foreign language.Statistically important differences have been found in learning motivation according to gender. Women are found to be less indifferent to foreign language learning, they are less bored in the learning process.
Keywords: motivation of learning; motivation of learning a foreign language; emotional well-being